Assessment of Knowledge and Practices of a Healthy Diet among a Selected Population of Diabetic Patients Attending the Diabetic Clinic in Colombo South Teaching Hospital - Hettiaratchi, U.P.K.; Pathirana, B.A.P.T.N. (My University, 2016)
Attached